Management of the extraction socket and timing of implant placement: Consensus report and clinical recommendations of group 3 of the XV European Workshop in Periodontology. (18th June 2019) - Tonetti, Maurizio S.; Jung, Ronald E.; Avila‐Ortiz, Gustavo; Blanco, Juan; Cosyn, Jan; Fickl, Stefan; Figuero, Elena; Goldstein, Moshe; Graziani, Filippo; Madianos, Phoebus; Molina, Ana; Nart, Jose; et al.
Abstract: Background: The transition from a tooth requiring extraction to its replacement (with a dental implant) requires a series of clinical decisions related to timing, approach, materials, cost‐effectiveness and the assessment of potential harm and patient preference. This workshop focused on the formulation of evidence‐based consensus statements and clinical recommendations. Methods: Four systematic reviews covering the areas of alveolar ridge preservation/bone grafting, immediate early and delayed implant placement and alveolar bone augmentation at the time of implant placement in a healed ridge formed the basis of the deliberations. The level of evidence supporting each consensus statement and its strength was described using a modification of the GRADE tool. Results: The evidence base for each of the relevant topics was assessed and summarized in 23 consensus statements and 12 specific clinical recommendations. The group emphasized that the evidence base mostly relates to single tooth extraction/replacement; hence, external validity/applicability to multiple extractions requires careful consideration. The group identified six considerations that should assist clinicians in clinical decision‐making: presence of infection, inability to achieve primary stability in the restoratively driven position, presence of a damaged alveolus, periodontal phenotype, aesthetic demands and systemic conditions. Conclusions: A substantial and expanding evidence base is available to assist clinicians with clinical decision‐making related to the transition from a tooth requiring extraction to its replacement with a dental implant. More high‐quality research is needed for the development of evidence‐based clinical guidelines.